Farming as an Act Grattitude Norms and Practices of Sustainability among Muslim Farmers in Blora, Central Java - Hasan, Ahmad Muwafi Nur; Bagir, Zainal Abidin; Akhda, Najmu Tsaqib (Universitas Gadjah Mada, 2025)
The body of literature on environmental studies suggest that sustainability in agricultural sector is not only a matter of technical agricultural management, but also the ideas, norms, or values that farmers hold, including those from religion. This cannot hold true more than the Indonesia context of religious society. Indonesia is an agricultural country where most of the population’s livelihood is agriculture, as demonstrated by the fact that 37.5% of the total land area is used for farming. Through an empirical study in Blora, Central Java, this article aims to examine and identify the norms, practices, and motivations of faith-based organic farming by Nahdlatul Ulama Agriculture Development Institute (LPPNU) Blora in promoting environmental and food sustainability. This study is based on a qualitative study using the theories of lived religion and religious creativity. Data was collected through semi-structured interviews with 13 individuals, including spiritual leaders, NU administrators, and NU organic farmers, and participant observation for three months. This article has two main findings. First, the religious norms and practices developed by LPPNU in organic farming in Blora express the principles of worship, stewardship of the earth, compassion for nature, self-reliance, and sustainability by making nutrient-rich organic matter fertilizer. Secondly, the primary motivations for farmers to switch to organic are personal health, soil health, and religiosity. Other motivations are influenced by institutional authority and religious reasons.